Power system reliability evaluation - Billinton, Roy (Gordon and Breach, 1970)
This edition features new chapters on the growing areas of Monte Carlo simulation and reliability economics. In addition, chapters cover the latest developments in techniques and their application to real problems. The text also explores the progress occurring in the structure, planning, and operation of real power systems due to changing ownership, regulation, and access.